Prospects of incubation in supporting agrobased industry: Evidence from Malaysian agricultural research and development institute / Sarpaneswaran Subramaniam - Sarpaneswaran, Subramaniam (2020)
Agricultural incubation system plays an essential role in fostering the national agriculture systems. This study is mainly based on a single public agricultural research institution in Malaysia, which is, Malaysian Agricultural Research and Development Institution (MARDI). The main objective of this study is to examine the relevance of incubator support system in fostering capabilities development of incubatees. In this regards, the selected four MARDI’s agro-based incubatees have been studied qualitatively via indepth interviews. The emphasis is on assessing the different supports system at different incubation stages since there is lacking comprehensive studies on monitoring the agrobased incubatee business performance during and post-incubation periods. The case studies provide useful insights into the learning process i.e. (knowledge creation, knowledge absorption, and knowledge dissemination) and capabilities building i.e. (marketing, product development, and production technology development) take place in driving incubatee business performance during and post-incubation periods. In addition, the study further examines the challenges faced by incubatees at different incubation phases to develop the essential capabilities in accelerating their business performance. The main findings from the case studies indicated that there are mismatches in terms of services rendered by MARDI incubators to incubatees during incubation period which are significantly hindering incubatee’s business performance. This study highlights the variation in terms of organisational learning and capabilities development between graduated and non-graduated incubatees that are significantly reflecting their business performance. The key findings show that in order to strengthen the MARDI incubation system to support new ventures in the agriculture sector, MARDI should advance crucial support services to incubatees particularly during post-incubation period.